The Nutri-Score for a Healthy Diet: Pros and Cons - Pauline Raoul; Emanuele Rinninella; Marco Cintoni; Vincenzina Mora; Maria Cristina Mele (Nutrimentum et Curae)
Packaging labels must provide comprehensible nutritional information for consumers and represent a crucial educational tool to prevent non-communicable diseases such as metabolic syndrome, cardiovascular diseases, and cancers. Since 2017, France and other European countries have adopted the 5-color Nutri-Score label. This review describes Nutri-Score and analyses the latest evidence over the last two years regarding the strengths and weaknesses of Nutri-Score. Although various recent large studies correlated the application of the Nutri-Score algorithm (the purchases of some healthy products) and the lower risk of developing chronic diseases, further studies are necessary to evaluate these relationships with a large range of products in a real-life supermarket. The validation of a unique front-packaging label model remains controversial, and to date, no consensus has been reached. Several aspects need to be improved in the algorithm, such as the consideration of the degree of processing and the presence of food additives. Probably, the combination of various front-of packages labels could be the solution. In any case, its validity should be assessed by European scientific food authorities such as EFSA with further large human studies in real-life purchase conditions.